Conservation Principles and Infill Design Analysis of De Mier Eat and Stay Surabaya - Josefira Jedine Santoso; Timoticin Kwanda (ATRIUM: Jurnal Arsitektur, 2023)
Darmo is an area in the city of Surabaya which rich in architecture from the Dutch colonial period. Based on the Regional Regulations of the City of Surabaya, not all buildings in the Darmo area are protected. A lot of the original buildings were being interfered with. De Mier Eat and Stay is an example of adaptive reuse in the Darmo area that collaborates preserved Dutch Indies-styled building with a new modern building to accommodate new functions. This paper examines how successful conservation and infill design principles are applied in De Mier Eat and Stay. The research method was conducted qualitatively through site visits and interviews with the designer. The data were then analyzed with a comparative table based on the literature. From this study, it can be concluded that the interventions done in the opening elements fulfill all four conservation principles. In contrast, the wall elements only fulfill three, and the floor elements didn’t fulfill at all. The Infill design was done using the contrast approach. Collaborating two eras of architecture through façade, proportion, materials, and the responses to surroundings creates a unique harmony in De Mier Eat and Stay.